Parametric optimization and performance analysis of a waste heat recovery system using Organic Rankine Cycle (ORC) - Zainol Abidin, N. H. H.; Saadon, Syamimi; Abu Talib, Abd Rahim (Institute of Physics Publishing, 2018)
Organic Rankine Cycle (ORC) has been proven to be the most effective solution to utilize fully the waste heat energy produced from manufacturing and power plant. In this paper, thermodynamic analysis and performance optimization of an ORC waste heat recovery system is performed for an aircraft engine and R245-fa is chosen as the refrigerant. The main concern of this study is to maximize the total heat transfer rate through the evaporator, thus the optimization of the Thrust Specific Fuel Consumption (TSFC) and the Specific Thrust of the engine can be performed. The main parameter to conduct the optimization is Turbine Inlet Temperature (TIT) and preheating temperature of R245fa. From the analysis, by increasing the Turbine Inlet Temperature and the preheating temperature, the TSFC and Specific Thrust of the engine can be optimized.